WACANA KEKUASAAN DAN KESEWENANGAN PEMERINTAH DALAM VIDEOKLIP BERTEMA KRITIK POLITIK - Royan Sianipar, Christheo; Saifudin, Windri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesia's socio-political dynamics in recent years reflect an increasingly complex power landscape, marked by democratic index decline, controversy over Constitutional Court Decision No. 90/PUU-XXI/2023, and various structural problems including corruption, nepotism, and weak law enforcement. This research analyzes the discourse of power and government arbitrariness constructed in three politically critical music videos: Republik Fufufafa by Slank, Bangun Orang Waras by Methosa, and Menteri Durmagati by Kajawi. The study focuses on three main perspectives: (1) the critical viewpoint embedded in the music and lyrics; (2) the construction of power and arbitrariness of rulers; and (3) the impact of such power on society. Using a descriptive qualitative method with a critical paradigm and Norman Fairclough's Critical Discourse Analysis (CDA) model covering three dimensions of text, discursive practice, and social practice, this study finds that all three music videos construct a critical discourse through the portrayal of state chaos arising from deviant power practices, the arbitrariness of rulers obtained through legal manipulation and nepotism, and the people as victims bearing the consequences of corruption across multiple sectors ranging from food, education, employment, to infrastructure. The study demonstrates that politically critical music videos can serve as an effective alternative medium for representing the relationship between power, the state, and society, while fostering public critical awareness.